Ionic‐Liquid Gating: Quantitative Determination on Ionic‐Liquid‐Gating Control of Interfacial Magnetism (Adv. Mater. 17/2017). Issue 17 (May 2017) - Zhao, Shishun; Zhou, Ziyao; Peng, Bin; Zhu, Mingmin; Feng, Mengmeng; Yang, Qu; Yan, Yuan; Ren, Wei; Ye, Zuo‐Guang; Liu, Yaohua; Liu, Ming
Abstract : Ionic‐liquid‐gating control of interfacial magnetic anisotropy in Au/[DEME]+[TFSI]‐/Co/SiO2 multilayer structures is quantitatively determined by the electron spin resonance method, as described in article number1606478 by Ziyao Zhou, Ming Liu and co‐workers. A reproducible, reversible ferromagnetic resonance field shift of 219 Oe at an applied voltage of 1.5 V, with a large ME tunability of 146 Oe V −1, is achieved, assisted by the electric double layers at the room temperature.